2019
DOI: 10.1002/ecs2.2790
|View full text |Cite
|
Sign up to set email alerts
|

Community regulation models as a framework for direct and indirect effects of climate change on species distributions

Abstract: Existing projections of climate change impacts focus primarily on direct abiotic impacts on individuals and populations. However, these models often ignore species interactions, which are vital for determining community composition and structure. To evaluate both direct and indirect effects of climate change on species distributions, we applied the Menge–Sutherland model, which describes the relative role of predation and environmental stress in regulating community structure. Using a space‐for‐time approach, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 140 publications
(245 reference statements)
0
13
0
Order By: Relevance
“…Additionally, while temperature is a primary driver of distribution patterns 102,103 , biotic resistance also plays a critical role 49 . Yet biotic interactions are, themselves, often altered by abiotic conditions 16,104 . Traits can act synergistically (for example, a drought causes reduced propagules), creating feedbacks that alter the magnitude of impacts.…”
Section: Challenges and Potential Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, while temperature is a primary driver of distribution patterns 102,103 , biotic resistance also plays a critical role 49 . Yet biotic interactions are, themselves, often altered by abiotic conditions 16,104 . Traits can act synergistically (for example, a drought causes reduced propagules), creating feedbacks that alter the magnitude of impacts.…”
Section: Challenges and Potential Limitationsmentioning
confidence: 99%
“…3 for an example) have assessed the community and ecosystem impacts of species tracking their climate niche into new areas. This research gap remains despite theoretical literature that recognizes the potential for impacts and the need for such research [14][15][16][17] . The lack of studies on range shift impacts is surprising given that the introduction and spread of new species is often viewed by ecologists through the lens of invasion biology, where the primary concern is the potential for negative impacts on the recipient community.…”
mentioning
confidence: 99%
“…We used SEM to explore the main factors that affect litter layer WSM and to assess how the variables were affected by the different factors. To use the SEM model, we rst conducted a principal component analysis (PCA) of the two data groups-biotic and abiotic-individually to reduce the dimensionality of the data (Wallingford and Sorte, 2019). We found that the rst two principal components accounted for 71% and 71%, and 79% of total variances in the three data groups, respectively (Table 4); therefore, in the SEM analyses, we used the standardized values of WSOC and WSN and the factor loadings of the rst two principal components of each group.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson et al, 2002;Hiscock et al, 2004;Morelissen & Harley, 2007;Harley, 2011;Meager et al, 2011;Kordas et al, 2015). Air and sea temperatures regulate spatio-temporal patterns of the whole in the intertidal zone by creating a gradient of environmental conditions (Sunday et al, 2019;Wallingford & Sorte, 2019). Higher temperatures reduce intertidal biodiversity, particularly PeerJ reviewing PDF | (2019:07:39107:3:0:CHECK 14 Nov 2019)…”
Section: Introductionmentioning
confidence: 99%